Mesenteric Lymph Node Recurrence of a Primary Colorectal Leiomyosarcoma. (23rd March 2020) - Beauchamp, Amélie; Hajjar, Roy; Khullar, Sharmila; Latour, Mathieu; Schwenter, Frank; Sebajang, Herawaty
Abstract : Primary colorectal leiomyosarcoma is an excessively rare entity. It is associated with an aggressive behavior and typically favor hematogenous spread. The current standard of care is surgical resection. A 49-year-old patient presented with a 2-month history of fever. A PET-scan revealed a hypermetabolic mass in the transverse colon, and colonoscopy confirmed a tumor. A right hemicolectomy was performed. Histopathological diagnosis was of a leiomyosarcoma. Fourteen months after the surgery, a follow-up abdominal scan revealed a 2 cm mesenteric lymph node that was hypermetabolic on PET-scan. The mesenteric lymph node was resected and histopathology confirmed a leiomyosarcoma metastasis. This case opens the controversy on the management of rare lymph node recurrences in colorectal leiomyosarcoma.